DIALEKTIKA FILOSOFIS IBN SINA DAN ARISTOTELES MENELUSURI FONDASI EPISTEMOLOGIS DALAM TEORI KOMUNIKASI LINTAS BUDAYA ISLAM-YUNANI - Mailin, Mailin; Siregar, Alya Rahmayani; Zulkarnain, Iskandar (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
This study examines the philosophical interaction between Ibn Sina and Aristotle within the framework of the theory of cross-cultural communication between Islam and Greece. By applying qualitative methods and text analysis, this study seeks to identify the epistemological foundations that underpin the thinking of the two philosophers, as well as explore the application of their ideas in the context of intercultural communication. Ibn Sina, known as Avicenna among Western thinkers, not only adopted but also enriched Aristotle's thought with an Islamic perspective, resulting in a distinctive synthesis between Greek philosophy and Islamic theology. This research emphasizes the importance of logic, ethics, and metaphysics in creating bridges of understanding between two different cultural traditions. Through in-depth analysis, this study shows how the concepts carried by the two philosophers can contribute to facing today's global communication challenges, including cultural pluralism and interreligious dialogue. Thus, this research focuses not only on the theoretical aspects, but also on the practical application of their thinking in the modern context. The findings of this study indicate that the philosophical dialogue between Ibn Sina and Aristotle contributed significantly to a broader epistemological understanding. In addition, the approach resulting from the interaction of their thoughts offers a deeper perspective in understanding the dynamics of cross-cultural communication. Thus, this study has the potential to enrich academic discourse on the relationship between philosophy and communication practice in an increasingly complex and diverse context.